Hemoglobin Examination and Education for Early Detection of Anemia in Pregnancy - Fathony, Zaiyidah; Amalia, Rizki; Lestari, Pratiwi Puji (UrbanGreen Central Media, 2021)
The prevalence of anemia in Indonesia is 21.7%, male is 18.4% and female is 23.9% higher. The proportion of anemia by age 15-24 years is 18.4% (Riskesdas, 2018). Anemia during pregnancy not only affects the mother but also the fetus. Pregnant women who suffer from severe anemia are at risk for bleeding during childbirth and death. This Community Service activity is located in the working area of ​​Sungai Tabuk III Health Center, precisely in Paku Alam Village. Activities for checking Hb (blood) for pregnant women and education about anemia in pregnant women will be held on October 16, 2021. it is known that there are 6 pregnant women who take part in community service activities in Paku Alam Sungai Tabuk Village, the majority of them are of reproductive age between 20 to 35 years. There are high risk pregnant women, namely grande multipara as much as 16.67% and there are 33.33% pregnant women with anemia detected. The scope of the examination and the provision of education is limited to only one kelurahan area so that it cannot cover all pregnant women. We hope to be able to carry out similar activities for a wider reach.